Learning grammar the ‘Monster’ Way ‘Monster Back to School-Parts of Speech Board Game’ / Angeline Ranjethamoney Vijayarajoo and Roslina Mohd Jani - Vijayarajoo, Angeline Ranjethamoney; Mohd Jani, Roslina (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Learning grammar can be difficult for learners but this can be changed through interactive activities. Language games are an excellent way to make learning grammar fun among learners Although the use of language games is not a new tool in the teaching and learning of grammar, employing the right game for a specific grammar item is vital. Hence, this study aims to experiment, using a language game - ‘Monster Back to School -Parts of Speech Board Game, in efforts to enhance the learning of the parts of speech more effectively. This game is designed to provide practice in identifying the parts of speech in the English Language, from word level, through sentence level to making decisions on whether the parts of speech have been correctly identified. By playing this game, it is believed that learners will be able to engage and learn grammar in a fun-filled way. Methodology comprised quantitative and qualitative methods, using a questionnaire and interview, with the participants, who were college students. The results of the survey demonstrate the effectiveness of the game in the identification and learning of parts of speech. The pedagogical implications are that suitable language games can enhance grammar competence.